Enhanced removal and valorization of CO2-adsorbent monoethanolamine by microalgae for green biomanufacturing - Zhiyong Liu; Nahui Hao; Chunqing He; Yuyong Hou; Tingfeng Cheng; Yinghao Wang; Qingling Liu; Qian Shen; Maliheh Safavi; Fangjian Chen; Zhihua Fan; Lei Zhao (Green Carbon, 2025)
Monoethanolamine (MEA) is a frequently utilized absorbent for CO2 capture in many settings, enabling biomanufacturing using carbon as the resource. Nevertheless, evidence indicates that MEA is toxic to biological systems, and its emissions can exacerbate ecosystem pollution. Therefore, it is imperative that disposal or valorization measures be implemented for effective green biomanufacturing with MEA as the absorbent. This study examined the removal of MEA by Haematococcus pluvialis (H. pluvialis), an astaxanthin-rich microalgae, and its effects on microalgal cells and related mechanisms. Approximately half of the initial MEA was metabolized by H. pluvialis, with the resulting metabolic intermediates including acetyl-CoA. The genes involved in MEA utilization exhibited a significant increase in expression, signifying a pivotal advancement in our understanding of its potential as a nutrient for microalgae. Moreover, the exposure of H. pluvialis to MEA resulted in notable alterations in cellular components, including a 21.7% increase in lipid content and a 27.8% increase in carbohydrate content. Notably, there was a 1.49-fold increase in astaxanthin content, which was accompanied by notable changes in cell morphology. In addition to the increase in astaxanthin production, the antioxidant system was activated to counteract the adverse effects of MEA-induced oxidative stress. Furthermore, enhanced biosynthesis of both carotenoids and fatty acids directly contributed to the elevated cellular astaxanthin levels achieved through MEA metabolism by H. pluvialis. These findings offer valuable insights into the treatment of CO2 absorbents using microalgae while simultaneously producing high-value and healthy products, which may prove beneficial for the development of sustainable solutions for green biomanufacturing.